2019
DOI: 10.1111/ijfs.14276
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐sensitive polyurethane (TSPU) film incorporated with carvacrol and cinnamyl aldehyde: antimicrobial activity, sustained release kinetics and potential use as food packaging for Cantonese‐style moon cake

Abstract: Temperature-sensitive polyurethane (TSPU) films incorporated with carvacrol and cinnamyl aldehyde were prepared for the potential use of food packaging. The antimicrobial properties and sustained release kinetics of carvacrol and cinnamyl aldehyde in TSPU film were investigated. Results indicated that cinnamyl aldehyde and carvacrol had favourable antimicrobial properties at relatively low addition ratio. The diffusion and release of carvacrol were linearly related to temperature and its addition ratio. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Eucalyptus oil ( Nameghi et al., 2019 ) and carvacrol ( Luna et al., 2010 ) are the representative plant oils used in the broiler productions and effectively prevent the occurrence of necrotic enteritis ( Sivarajan et al., 2017 ). Cinnamyl aldehyde and capsaicin were also shown to present anti-inflammatory functions ( Dong et al., 2019 ). The effects of combined essential oils on broiler production were seldom acquired, and whether combinations of essential oils performed a better than when not combined needs further examination.…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus oil ( Nameghi et al., 2019 ) and carvacrol ( Luna et al., 2010 ) are the representative plant oils used in the broiler productions and effectively prevent the occurrence of necrotic enteritis ( Sivarajan et al., 2017 ). Cinnamyl aldehyde and capsaicin were also shown to present anti-inflammatory functions ( Dong et al., 2019 ). The effects of combined essential oils on broiler production were seldom acquired, and whether combinations of essential oils performed a better than when not combined needs further examination.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature‐sensitive polyurethane (TSPU) films containing cinnamyl aldehyde and carvacrol were used to create a packaging material that could be used for Cantonese‐style moon cakes. The comparative study of TSPU films and common polyethylene food packaging films revealed that the TSPU films have a greater influence on the increased shelf life of Cantonese‐style cake because of their effective microbial growth inhibition and decreased lipid oxidation (Dong, He, Xiao, & Li, 2020). A chitosan film containing potassium sorbate or vanillin, which acts as a food wrapping with antimicrobial property, was used to increase the shelf life of the butter cake.…”
Section: Application Of Antimicrobial Packagingmentioning
confidence: 99%
“…Additional examples range from the use of naturally occurring small molecules such as curcumin (Curcuma longa) in polyacrylonitrile (PAN) films (Fig. 6a; 187 ), carvacrol and cinnamyl aldehyde in temperature sensitive polyurethane films; 188 tannic acid 189 coatings in SyP catheters.…”
Section: Chemical Functionalization For the Fabrication Of Antimicrobial Surfacesmentioning
confidence: 99%